A new rare species of Arcynopteryx (Plecoptera: Perlodidae) from the basin of Lake Baikal (Russia) - Teslenko, Valentina A.; Zhiltzova, Lidia A. (Zootaxa, 2012)
A new species of Plecoptera Arcynopteryx angarensis sp. n. is described, illustrated and compared with congeners. Arcynopteryx angarensis is known only from historical records at the source of the Angara River (Lake Baikal Basin). It has not been collected since 1930.